A semantic analysis of Ninez Cacho Olivares language in her columns from September 1992 to February 1993 - Sanchez, Nilda Tomas; Ravina, Maria Clara V. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1993)
This study aimed to find out how Niñes Cacho Olivares uses and manipulates the English language in her columns. Its aims were to find out what kind of writing style she employs in giving her opinions, and in what way she uses this style in her writing. The researcher assumed that the writer has certain kind of writing style in her columns in order to create more impact on the readers. This semantic analysis used the theory of presupposition. This theory enabled the researcher to analyze in-depth the sentences based on their presuppositions. The results of this study were: The writer uses a kind of writing style through her use of words in the sentences. There are certain words in the sentences which generate their presuppositions. In turn, these presuppositions when carefully scrutinized contain embedded meanings. The embedded meanings are the ideas and message the writer wants to express. The style of the writer affects the impact of her columns on the readers. They easilly realte themselves to her because she captures the people's feelings towards the critical condition of the nation today. Her style enhances the force of expressing her opinions. Her sharp assessments are embedded in the presuppositions of the sentences. Therefore, the hypothesis was confirmed.
Thesis (Bachelor of Arts in English Studies: Language)--University of the Philippines Diliman
Includes bibliographical references (pages 53-54).